On the conditions for the cooperative relations between family businesses: The role of trust - Hadjielias, Elias; Poutziouris, Panikkos Zata (My University, 2015)
Purpose – The purpose of this paper is to investigate the conditions underpinning the cooperative relationships between family businesses. The role of trust is also explored, given the focus on informal conditions nested within the cooperation between firms. Design/methodology/approach – A case study research method is adopted in this paper. This research is conducted within a cooperative association in Cyprus where 40 retail family businesses trade under the same brand. Findings – The findings suggest that cooperation between family businesses emerges and unfolds as a result of the presence and interrelationships between a number of critical conditions: trust, altruism, collective thinking, stewardship, friendship, and family values congruence. The work illustrates that trust becomes a catalyst to the emergence and maintenance of cooperative relations between family businesses. Trust between family leaders is important in building altruism, collective thinking, and stewardship norms amongst them, and helps in sustaining the cooperation between their respective firms. At the same time, trust (stemming from past friendship and values congruence between diverse family leaders) becomes important in bringing family businesses to cooperate together at first instance. Further, the findings stress the role of critical events and self-interest in moderating the role and influence of trust on the cooperation between family businesses. Originality/value – This paper contributes to the family business field through new knowledge on the relations between family businesses and the unique conditions that shape their long-term cooperation.
Keywords: Cooperative inter-firm relations; Cooperatives; Family business; Inter-firm cooperation; Trust